Production of biopolymers from food waste: Constrains and perspectives. (October 2022) - Gautam, Krishna; Vishvakarma, Reena; Sharma, Poonam; Singh, Amarnath; Kumar Gaur, Vivek; Varjani, Sunita; Kumar Srivastava, Janmejai
Graphical abstract: Highlights: Food waste can serve as economic substrate for biopolymer production. Combination of valorization strategies was more efficient than individual ones. Biopolymers from food waste have applications from healthcare to food industry. Abstract: Food is an essential commodity for the survival of any form of life on earth. Yet generation of plethora of food waste has significantly elevated the global concern for food scarcity, human and environment deterioration. Also, increasing use of polymers derived from petroleum hydrocarbons has elevated the concerns towards the depletion of this non-renewable resource. In this review, the use of waste food for the production of bio-polymers and their associated challenges has been thoroughly investigated using scientometric analysis. Various categories of food waste including fruit, vegetable, and oily waste can be employed for the production of different biopolymers including polyhydroxyalkanoates, starch, cellulose, collagen and others. The advances in the production of biopolymers through chemical, microbial or enzymatic process that increases the acceptability of these biopolymers has been reviewed. The comprehensive compiled information may assist researchers for addressing and solving the issues pertaining to food wastage and fossil fuel depletion.